Improving Students’ Reading Comprehension by Using Sq3r Method in Vocational High School at SMK AL Maksum Langkat - Fernando De Napoli Marpaung; Edi Suprayetno; Supriadi (LPPM STKIP AL MAKSUM, 2022)
SQ3R stands for Survey, Question, Read, Recite/Recall and Review. In this study,the writer used an action research. For collecting the data, the writer used testand observation. The data sources are the 10 th grade of SMK AL MaksumLangkat at TKJ department which consists of 32 students and an English Teacheras the observer. Phase I consists of planning, action, observation and reflection.Phase II added by the revision of phase I. Based on the results of the study, inphase I the percentage of students who achieved Minimum AccomplishmentCriteria 75 was 65%. In other words, 21 students had achieved MinimumAccomplishment Criteria, while 11 students had not reached MAC. In phase II, allof students have reached Minimum Accomplishment Criteria. The result showed,in phase II all of the students could comprehend the text and determine the mainidea and reached Minimum Accomplishment Criteria in reading it is 75. Thus, thehypothesis in this research is acceptable. It means, there is a significant improvingin using SQ3R to increase the students’ reading comprehension at the 10 th gradeof SMK AL Maksum Langkat at TKJ department. Therefore, the research wasdiscontinued on the second phase.